Penguatan Akuntabilitas Dana Sosial dan Kepercayaan Publik: Kajian Transitivitas - Suparno, Darsita; Thamrin, Husni; Izzah Chairul, Aqidatul; Ilham Firizkillah Chairul, Muhammad; Atih, Idris (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2025)
Misuse of social funds often occurs in humanitarian organizations, including Aksi Cepat Tunjung (ACT), which is suspected of channeling social funds to the al-Qaeda terrorist network. This research aims to analyze transitivity patterns in dialogue between legal experts, international relations and PPATK representatives on the YouTube platform, especially in programs that discuss this case. Research data in the form of dialogue taken from the Medcom.id YouTube channel was analyzed qualitatively. The research results show the dominance of material processes that reflect real actions such as transactions and sending funds by ACT to organizations that are indicated as terrorists. Relational and mental processes reveal relationships between entities and understanding of the issue. Verbal, behavioral, and existential processes provide additional context, including community reactions, reporting, and the existence of conflict. The transitivity patterns found include Actor structure (ACT) + Material Process (carried out) + Goal (the organization) + Circumstance (how many times). In addition, the existential process is analyzed through the pattern of Existential Process (there is) + Goal (some transaction), as well as material processes in the structure of Actor (me) + Material Process (giving) + Goal (that information) + Circumstance (detail). These findings underscore the importance of transparency in the management of social funds and its impact on public trust and national security